Fighting for a Lost Cause? The Germanophile Newspaper La Unión in Neutral Argentina, 1914-1918 - Tato, María Inés (2017)
During the First World War, the belligerent powers attempted to recruit the neutral States to support their cause. Their citizens abroad and propaganda were a crucial part of their strategy. This article examines a German propaganda initiative addressed to Latin America through a case study focused on Argentina: the daily newspaper La Unión. This publication – developed by the local German community with the support of its government – sought to neutralize the allegiance to the Allied cause that prevailed in public opinion due to demographic, economic, cultural, and informational factors. This article reconstructs the obstacles faced by La Unión, as well as its objectives and strategies, and offers an assessment of its achievements.